2022
DOI: 10.3389/fpubh.2022.993946
|View full text |Cite
|
Sign up to set email alerts
|

Association between hospital legal constructions and medical disputes: A multi-center analysis of 130 tertiary hospitals in Hunan Province, China

Abstract: BackgroundMedical disputes are common in hospitals and a major challenge for the operations of medical institutions. However, few studies have looked into the association between medical disputes and hospital legal constructions. The purpose of the study was to investigate the relationship between hospital legal constructions and medical disputes, and it also aimed to develop a nomogram to estimate the likelihood of medical disputes.MethodsBetween July and September 2021, 2,716 administrators from 130 hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…We identified several unmodifiable risk factors that contribute to the occurrence of medical disputes among healthcare professionals. These findings are consistent with previous studies, 2,3,15,[21][22][23] which further strengthen their significance. Recognizing and addressing these unmodifiable risk factors can empower healthcare institutions and policymakers to develop targeted interventions and strategies that effectively address the specific challenges faced by healthcare professionals at higher risk of medical disputes.…”
Section: Implications For Healthcare Institutions and Policymakerssupporting
confidence: 93%
See 2 more Smart Citations
“…We identified several unmodifiable risk factors that contribute to the occurrence of medical disputes among healthcare professionals. These findings are consistent with previous studies, 2,3,15,[21][22][23] which further strengthen their significance. Recognizing and addressing these unmodifiable risk factors can empower healthcare institutions and policymakers to develop targeted interventions and strategies that effectively address the specific challenges faced by healthcare professionals at higher risk of medical disputes.…”
Section: Implications For Healthcare Institutions and Policymakerssupporting
confidence: 93%
“…Previous studies have also shed light on this matter, with a study among hospital administrators reporting a prevalence of 41.53%. 2 Additionally, varying populations and regions have exhibited a prevalence ranging from 34.1% to 46.06%. 15 The significance of these findings was further underscored by a nationwide survey conducted in China in 2021, which revealed that 31.06% of doctors have grappled with medical disputes involving patients.…”
Section: Epidemiology Of Medical Disputesmentioning
confidence: 99%
See 1 more Smart Citation
“…To promote the transformation of public hospitals from "disease-centered" to "patient-centered", it is important that they establish and improve medical services, such as high-quality nursing services and satisfaction management, allow the support of information technology in medical care, constantly enhance the continuity of medical services, integrate patient safety management into every link of hospital management, achieve continuous improvement, and form a new service model of public hospitals. At the same time, it is important to further improve medical services and patients' experiences to improve doctor-patient communication and medical dispute prevention and handling mechanisms [25][26][27]. Therefore, high-level hospitals with strong in uence and radiation effects and outstanding comprehensive advantages should be selected to build provincial regional medical centers, improve the comprehensive carrying capacity of medical and health services in different regions, better meet the needs of medical services in the region and reduce the cross-regional ow of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, research on medical dispute resolution methods has focused more on litigation [29][30][31][32][33][34][35]; some studies have emphasized the role of mediation, but research into the characteristics, e ciency, and in uencing factors of TPM in resolving medical disputes using a large number of detailed cases is lacking [19,27,29,36]. Therefore, we analyzed TPM practices using data from 5,948 cases in Chinese public hospitals from 2014 to 2019 in Gansu, a western province in China.…”
Section: Introductionmentioning
confidence: 99%